(3eLehYI aj GdgfOSIs - (3eGfGdGhSs
(3ChdgG (B:s
(3Cbhd HYO MeO Gddg hGdKfGA Ydjg HeG jdjb Hg Efi cfJ CQjO Cf CMQQ GdcJH GdehSheI HGdeJhSWGJ CYfi GdcJH GdJi ef TCfgG Cf JJhSW ai GdJQJjH GdJYdjei Hjf cJGH GdGUhd dEbdjOS hHjf cJGH GdeLSWi dHWdjehS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B143s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , HgG NQe s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs